2011
DOI: 10.1038/nphys2149
|View full text |Cite
|
Sign up to set email alerts
|

Coherent control of three-spin states in a triple quantum dot

Abstract: It has been suggested that triple quantum dots may provide additional tools and functionalities. These include encoding information either to obtain protection from decoherence or to permit all-electrical operation 5 , efficient spin busing across a quantum circuit 6 , and to enable quantum error correction using the three-spin Greenberger-Horn-Zeilinger quantum state. Towards these goals we demonstrate coherent manipulation of two interacting three-spin states. We employ the Landau-Zener-Stückelberg 7,8 appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
313
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(320 citation statements)
references
References 21 publications
7
313
0
Order By: Relevance
“…Here we examine the validity range of the Gaussian approximation, as the number of fluctuators is increased, and its dependence on the number of control pulses. As current experimental efforts are focused on more complicated QD structures, such as two coupled double QDs, 26,35 and three-spin qubits in triple-dots, [36][37][38] the resulting larger devices are expected to have a noisier charge environment. Understanding how qubit decoherence scales with the number of TLFs is therefore important.…”
Section: Introductionmentioning
confidence: 99%
“…Here we examine the validity range of the Gaussian approximation, as the number of fluctuators is increased, and its dependence on the number of control pulses. As current experimental efforts are focused on more complicated QD structures, such as two coupled double QDs, 26,35 and three-spin qubits in triple-dots, [36][37][38] the resulting larger devices are expected to have a noisier charge environment. Understanding how qubit decoherence scales with the number of TLFs is therefore important.…”
Section: Introductionmentioning
confidence: 99%
“…Three coherently coupled quantum dots with three spins attracted interest in the hope to construct a qubit using purely electrically gated manipulations [9,10]. Most recently, for a triple quantum dot (TQD) structure it was shown that bipolar spin blockade can become a relevant quantum coherent mechanism [11].…”
Section: Introductionmentioning
confidence: 99%
“…These have been demonstrated repeatedly by numerous groups in the context of spintronic quantum computing [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. It is currently a well-established art.…”
Section: Single Spin Logic (Ssl)mentioning
confidence: 98%